Regenerasi Embriogenesis Somatik pada Beberapa Klon Kakao Indonesia dari Eksplan Bunga - Avivi, Sholeh; Prawoto, Adi; Oetami, Reny Fauziah (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2010)
<!-- /* Font Definitions */ @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:Calibri; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; mso-ansi-language:IN; mso-no-proof:yes;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> This research was aimed to observe the response of different clones and speciﬁ c organs due to the somatic embryogenesis regeneration. It was arranged in factorial randomized completely design with three replication. The ﬁ rst factor was cocoa clones i.e. ICCRI 01, ICCRI 02, ICCRI 03, ICCRI 04, KW 514, RCC72, and Sca 6. The second factor was ﬂ ower parts i.e. petal, staminode and anther. Every explant was regenerated on initiation, induction, multiplication and rooting media. Almost all treatments showed high response of embryogenic calli which range 89.5 to 100% at initial stage, but different results were found at the following process of somatic embryogenesis. The experiment showed that each clones and each different part of ﬂ ower had different response to somatic embryogenesis. The highest response of the explant number resulted from Sca 6 clone, which produce 35.8% embryo with average number of embryo per explant (1.34) followed by RCC 72 (28.4%, averaged 0.7) ICCRI 03 (24.7%, averaged 1.3) ICCRI 04 (18.6%, averaged 0.6). While ICCRI 02 showed the lowest responsive clone. Especially for ICCRI 01, 55.8% explant was rooted and only 1.3% explant producing embryo. The highest response of somatic embryo was resulted form petal. Keywords: somatic embryogenesis, ﬂ ower explant, Cocoa